2022
DOI: 10.1038/s41598-022-06218-3
|View full text |Cite
|
Sign up to set email alerts
|

A proficient approach to forecast COVID-19 spread via optimized dynamic machine learning models

Abstract: This study aims to develop an assumption-free data-driven model to accurately forecast COVID-19 spread. Towards this end, we firstly employed Bayesian optimization to tune the Gaussian process regression (GPR) hyperparameters to develop an efficient GPR-based model for forecasting the recovered and confirmed COVID-19 cases in two highly impacted countries, India and Brazil. However, machine learning models do not consider the time dependency in the COVID-19 data series. Here, dynamic information has been taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 68 publications
0
40
0
Order By: Relevance
“…(2022) employed linear regression, a multi-layer perceptron (MLP), and vector auto regression to predict various COVID-19 outbreaks in India. The random forest, support vector machine (SVM), and other machine-learning algorithms were used in a study by Alali et al. (2022) for predicting the confirmed and recovered COVID-19 cases in India and Brazil.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2022) employed linear regression, a multi-layer perceptron (MLP), and vector auto regression to predict various COVID-19 outbreaks in India. The random forest, support vector machine (SVM), and other machine-learning algorithms were used in a study by Alali et al. (2022) for predicting the confirmed and recovered COVID-19 cases in India and Brazil.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, data-driven models require enormous amounts of data to model behavior and improve learning and are computationally expensive. ML models used for COVID-19 forecasting, as discussed in [49], [50], do not efficiently exploit the fact that the data is time-series data. It does not include continuous feedback and does not take that into account when forecasting.…”
Section: Comparative Analysismentioning
confidence: 99%
“…Zeroual et al [31] applied five deep learning methods to the global forecast of daily new confirmed and recovered cases of COVID-19 based on a small volume of data. Yasminah et al [32] developed a new method to predict how COVID-19 will spread.…”
Section: B Overview Of Related Researchmentioning
confidence: 99%